MicroRNAs: Not “Fine-Tuners” but Key Regulators of Neuronal Development and Function - Davis, Gregory M.; Haas, Matilda A.; Pocock, Roger (Frontiers in Neurology, 2015)
microRNAs (miRNAs) are a class of short non-coding RNAs that operate as prominent post-transcriptional regulators of eukaryotic gene expression. miRNAs are abundantly expressed in the brain of most animals and exert diverse roles. The anatomical and functional complexity of brain requires the precise coordination of multi-layered gene regulatory networks. The flexibility, speed and reversibility of miRNA function provide precise temporal and spatial gene regulatory capabilities that are crucial for the correct functioning of the brain. Studies have shown that the underlying molecular mechanisms controlled by miRNAs in the nervous systems of invertebrate and vertebrate models are remarkably conserved in humans. We endeavour to provide insight into the roles of miRNAs in the nervous systems of these model organisms and discuss how such information may be used to inform regarding diseases of the human brain.